The Effectiveness of Two Proposed Strategies Based on the Dimensions of Logical Thinking in Developing Mental Traits among Students of Psychological and Educational Sciences - Ahmed, Ahmed Bassem; Muhammad, Raad Khalaf (Journal of Tikrit University for Humanities, 2025)
The researcher followed the procedures of the experimental method and adopted the experimental design with pre- and post-tests and partial control for equal groups. The research sample was chosen from the third year students in the Department of Educational and Psychological Sciences in Tikrit University. They were 153 male and female students. They were divided into two groups. The first group is the experimental. It included 51 male and female students. The second is the control group. It consisted of 50 male and female students. The researcher made equivalence of the two research groups in some variables (the chronological age of the students calculated in months, intelligence, GPA of the previous academic year, gender, and the pre-test mental traits scale). The mental traits scale was prepared, in its final form, consisting of 28 items with 7 items for each field, and the researcher verified its validity, discrimination, and stability. The researcher used the statistical package (spss) and after analyzing the results statistically, the results showed the positivity of the independent variable (the two proposed strategies based on the dimensions of logical thinking). The researcher reached a number of conclusions and presented a set of recommendations and proposals.